Imunogenicidade de bacterinas anti-leptospiras para bovinos produzidas no Brasil, 2006/7 - Rogerio Oliveira Rodrigues (2008)
In the present study the levels of antibodies than ten bacterins comprising nine commercial and a experimental monovalent, produced with serovar Hardjoprajiitino sample Norma, were evaluated using up the microagglutination test (MAT) and an enzyme immunoassay (ELISA) indirect. Levels of protection conferred by bacterins obtained in the test inhibition of growth (TGI) and ELISA were correlated. For the TGI with serovar Hardjoprajiitino sample Norma were chosen important times in terms of IgG concentration (Days 60, 240, 270, 330 and 420). At a test was developed immunoassay indirect, using anti-IgG conjugated total to measure the levels of the immunoglobulin G class given by bacterins using three different samples (Hardjoprajiitino, Hardjoprajiitino sample Norma and Hardjobovis). It was used MAT exclusively to measure the levels of immunoglobulins in Class M using the three samples above said. We results showed that all bacterins produce some kind of answer, but only on days 60 and 270 achieved levels of protective antibodies not reaching all the animals used. The groups had not vaccinated same uniformity of response of antibodies suggesting the need to increase the concentration of serovar Hardjo to improve the immune response. The protocols for multivalent vaccines should be reviewed so that the Hardjo present serological response appropriate for revaccination six months